Angkak Infusion for Postpartum Recovery: Impact on Uterine Involution and Hemoglobin Levels - Senditya Mayasari; Waifti Amalia (An Idea Health Journal, 2026)
Background: Postpartum anemia and delayed uterine involution may hinder maternal recovery and increase postpartum morbidity. Angkak (Monascus purpureus-fermented red rice) contains iron, amino acids, antioxidants, and bioactive compounds that may support hemoglobin synthesis, erythropoiesis, and tissue repair. However, evidence regarding its use among postpartum mothers remains limited. Aim this study to assess changes in uterine involution and hemoglobin levels among postpartum mothers after consuming angkak infusion. Methods: A quasi-experimental one-group pre–post study was conducted among 25 postpartum mothers. Participants consumed 3 g of angkak infused in 150 mL of warm water daily for 14 days. Fundal height was measured on postpartum days 1, 7, and 14, while hemoglobin levels were assessed on days 1 and 14. Data were analyzed using the Wilcoxon signed-rank test and paired sample t-test. Result: Mean fundal height decreased from 16.84 cm on day 1 to 11.80 cm on day 7 and approximately 7–8 cm on day 14. Mean hemoglobin levels increased from 10.42 g/dL to 11.72 g/dL. Both changes were statistically significant. No adverse effects were reported during the intervention. Conclusion: Daily angkak infusion for 14 days was associated with improved uterine involution and increased hemoglobin levels among postpartum mothers. However, due to the absence of a control group, causal conclusions cannot be established. Further controlled studies with larger samples are recommended.